Usability Methodologies and Data Selection: Assessing the Usability techniques on Educational Websites - Abdulrahman, Ayub Othman; Hama Rawf, Karwan Mahdi (International Journal of Electronics and Communications Systems, 2022)
The purpose of an educational website is to efficiently provide up-to-date services and resources to students, faculty, and staff. However, the needs of university students are not always prioritized throughout the design phase of websites; instead, technological considerations, organizational concerns, and commercial goals may all drive the process. When it comes to meeting the demands of the target audience, website designers often fall short. At the same time, visitors may encounter a wide variety of usability issues while visiting the sites. Thus, the purpose of this study is to examine the efficacy of different approaches to evaluating the usability of university websites from the viewpoint of their target audiences via user-based testing and questionnaire methods involving actual users. The outcomes, which are based on data from tests conducted in real time, outline the difficulties and advantages associated with each strategy. Both a user-based test and a questionnaire, which are both trustworthy evaluation methodologies, were used in the process of analyzing and evaluating the websites.